Optimization of the Distance between Two Adjacent Multi-Story Buildings by Calculating the Earthquake Effect in Yogyakarta - Harsoyo, Yoga Aprianto Harsoyo (International Journal of Integrated Engineering, 2020)
Neo Malioboro and Malioboro Suite Hotels are two adjacent multi-story buildings in Yogyakarta with a fairly close distance of 2.5m (Lx) between their structures. Considering that Yogyakarta is an area prone to earthquakes, the relatively close distance between the two hotels has triggered research interest. The research was carried out by taking hotel planning data in the form of structural and architectural drawings modeled in SAP2000.14 to obtain structural behavior toward existing designs such as natural shear periods, base shear, mass participation, and to obtain deviation values between floors (drift ratio) and the center of mass deflection (Î´). The largest deviation value of the two hotels in the joint reviewed occurred on the top floor, with the maximum deviation value of 0.440m (Î´M1) for Neo Malioboro and 0.412m (Î´M2) for Malioboro Suite. The minimum deflection distance between the two hotels was 0.602m (Î´MT), resulting in the minimum separation distance for the two hotels of 1.454m. The results revealed that the distance of the two hotels was in a safe condition because it was greater than the required minimum separation distance of 2.5m > 1.454m.